Oral health practices among 10-15 years of government school children in Chengalpattu district, India: a cross-sectional survey - K., Indrapriyadharshini; S., Vishnu Prasad; J., Mahesh; V., Magdaline Joshey; P., Monika; S., Nikitha (International Journal Of Community Medicine And Public Health, 2022)
Background: Oral health is a fundamental part of the general health and well-being of an individual. Oral hygiene refers to the practice of maintaining a clean oral cavity to prevent dental problems like dental cavities, bad breath, gingivitis, and periodontitis. Aim was to assess oral health practices among 10-15 years of government school children in Chengalpattu district, India. Methods: This cross-sectional study included 1500 government school children aged 10-15 years based on the guidelines of the strengthening the reporting of observational studies in epidemiology. Each child was asked about the dental hygiene practices. Results: The study population was composed of 545 (36.3%) participants who belonged to the 10-12-year-old category and 955 (63.7%) belonged to the 13-15 years category. While assessing the oral hygiene practices of the children, 86.1% of children used toothbrush and toothpaste as oral hygiene aids. In our study more than half of the students 59% reported that they brush only in the morning that 32.8% of children felt stinky sometimes in their oral cavity. Only around 28.5% had used the service of a dentist during the last 6 months and about 12.8% in the last 1 year. Conclusions: The study results concluded that oral hygiene practices were enhanced among male children when compared to female children and showed a positive attitude in preserving appropriate oral health.